Suppressed Kondo effect and Kosterlitz–Thouless-type phase transition induced by level difference in a triple dot device. (1st September 2017) - Xiong, Yong-Chen; Huang, Hai-Ming; Zhao, Wen-Lei; Laref, Amel
Abstract: Quantum dot system provides an ideal platform for quantum information processing, within which to demonstrate the quantum states is one of the most important issue for quantum simulation and quantum computation. In this paper, we report a peculiar electron state in a parallel triple dot device where the Ruderman–Kittel–Kasuya–Yosida interaction is invalid when the level differences of the dots sweep into appropriate regime. This extraordinary tendency then results in an antiferromagnetic spin coupling between two of the dots and may lead to zero or full conductance, relying deeply on the relation of the two level spacings. e.g. when the level differences are kept equal, the Kondo effect is totally suppressed although the dots are triply occupied, since in this case a local inter-dot transport loop is found to play an important role in the transmission coefficient. By contrast, when the differences are retained symmetric, the Kondo peak reaches nearly to its unitary limit, owing to that the inter-dot transport process is significantly suppressed. To approach these problems, voltage controllable quantum phase transitions of Kosterlitz-Thouless type and first order are shown, and possible pictures related to the many-body effect and the effective Kondo model are given.